The Dynamic Nonsubstitution Theorem - Mirrlees, J. A. (Review of Economic Studies, 1969)
Journal Article The Dynamic Nonsubstitution Theorem Get access J. A. Mirrlees J. A. Mirrlees Nuffield College, Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 67–76, https://doi.org/10.2307/2296343 Published: 01 January 1969 Article history Received: 07 February 1968 Revision received: 31 July 1968 Published: 01 January 1969